CORSUS Accounting Information System and Internal Control Effectiveness: An Empirical Study at Yes Brebes Salted Egg Store - Dina Mei Liana; Bahri Kamal; Imam Hasan (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study investigates the implementation of the Corsus Accounting Information System (AIS) in enhancing internal control effectiveness at Yes Brebes Salted Egg Store. Employing a qualitative descriptive approach, data were collected through field observation, semi-structured interviews, and documentation analysis. The findings reveal that while Corsus adequately supports transaction recording and inventory management, significant internal control deficiencies persist across three dimensions: unclear functional role separation, insufficient workforce competency due to the absence of structured training programs, and technical constraints including on-premise server limitations and the lack of automated data backup. The evaluation indicates that only the authorization and recording element demonstrates partial compliance, while organizational structure, sound operational practices, and human resource competency remain inadequate. This study recommends organizational restructuring, systematic employee training, and a transition toward cloud-based infrastructure with automated backup capabilities to strengthen overall internal control effectiveness